EVALUASI PRINSIP GOOD GOVERNANCE SEBAGAI UPAYA PENCEGAHAN FRAUD PENGELOLAAN DANA DESA DI DESA KEDUNGREJO KABUPATEN NGANJUK - Sarwendah, Riris Sinta (Universitas Nusantara PGRI Kediri, 2023)
This study aims to evaluate the application of the principles of good governance in the village government of Kedungrejo and to identify whether Fraud prevention measures have been carried out properly. This research uses descriptive research with a qualitative approach. Primary data was obtained through interviews and observation, while secondary data was collected through documentation. Thus, this study will provide a detailed description of the application of the principles of good governance and the obstacles that may be encountered in preventing Fraud in managing village funds in Kedungrejo Village, Nganjuk Regency. the data obtained, choosing the main or important things, and removing unnecessary ones so that it can make it easier for researchers to draw conclusions. The results of the research are that in the village of Kedungrejo it has implemented good governance or good governance and no acts of Fraud have been found by the government of the village of Kedungrejo.